Baltoscandian margin, Sveconorwegian crust lost by subduction during Caledonian collisional orogeny - Gee, David G.; Andréasson, Per Gunnar; Li, Yuan; Krill, Allan (GFF, 2017)
Underthrusting of Laurentia by the continental margin of Baltica during Caledonian orogeny resulted in the lateral emplacement of Iapetus Ocean-related terranes of the Upper Allochthon at least 500 km onto Baltica. The underlying Lower and Middle allochthons of the Baltoscandian margin mostly comprise Cryogenian, Ediacaran and Cambro-Silurian sedimentary successions; basement to these formations are present only as minor, isolated fragments, except at the base of the Middle Allochthon and within the underlying windows. The upper parts of the Middle Allochthon are notable for the presence of early Ediacaran dyke-swarms and other components of the Baltoscandian continent–ocean transition zone (COT). New data are presented here on the c. 610 Ma age of the COT-related dolerites in the Kalak Nappe Complex in Northern Norway and also on detrital zircons in the underlying Laksefjord and Gaissa nappes. The former confirms that the Baltoscandian COT has a similar age along the length of the orogen; the latter shows that the detrital zircon signatures in the Lower and Middle allochthons are comparable throughout the orogen. These sedimentary rocks have dominating populations of Mesoproterozoic to latest Palaeoproterozoic zircons similar to those from southern parts of the orogen, where Sveconorwegian complexes comprise the basement to the Caledonides. Thus, they help define the probable character and age of the crystalline basement that existed along this outer margin of Baltica during the Neoproterozoic, continental lower crust that was partly subducted during Ordovician continent-arc collision and subsequently lost beneath Laurentia during the 50 million years of Scandian collisional orogeny.